Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.infsof.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A framework for pathologies of message sequence charts

Abstract: Context: It is known that a Message Sequence Chart (MSC) specification can contain different types of pathology. However, definitions of different types of pathology and the problems caused by pathologies are unclear, let alone the relationships between them. In this circumstance, it can be problematic for software engineers to accurately predict the possible problems that may exist in implementations of MSC specifications and to trace back to the design problems in MSC specifications from the observed problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
(158 reference statements)
1
8
0
Order By: Relevance
“…This complements previous results suggesting that the semantics of scenario-based models can be difficult to understand, leading to the potential for subtle mistakes [18]. A tester wishing to base testing on MSCs must consider the semantic issue and the results in this paper also show that the set of features used can have another significant practical effect in that it influences the computational complexity of the Oracle Problem.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This complements previous results suggesting that the semantics of scenario-based models can be difficult to understand, leading to the potential for subtle mistakes [18]. A tester wishing to base testing on MSCs must consider the semantic issue and the results in this paper also show that the set of features used can have another significant practical effect in that it influences the computational complexity of the Oracle Problem.…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown that the notion of a controllability problem when testing from an MSC specification is related to MSC pathologies [18]. In this paper, we discuss another critical issue in conformance testing with MSCs: the Oracle Problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSC operators and the hierarchical composition of HMSCs are similar to our approach. However, [15] reveals "pathologies" in MSCs, due to defective MSC specifications. These pathologies mainly affect synchronization issues.…”
Section: Related Workmentioning
confidence: 99%
“…This is in contrast to other popular behaviour models such as Finite State Machines (FSMs) and Input/Output Labelled Transition Systems (IOLTSs) [22,23,24,25]. This seems surprising since there has been much interest in the use of MSCs and analysing MSCs to, for example, find pathologies [26,4,27,28,29,30,31,32]. As MSCs are popular in modelling distributed systems, they have the potential to play an important role in MBT for distributed systems including systems based on grid and cloud technologies.…”
Section: Introductionmentioning
confidence: 98%